2016
DOI: 10.1002/jsfa.8071
|View full text |Cite
|
Sign up to set email alerts
|

Higher bioavailability of iron from whole wheat bread compared with iron‐fortified white breads in caco‐2 cell model: an experimental study

Abstract: Iron from unfortified whole wheat bread is more bioavailable than from three types of iron-fortified breads. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Furthermore, human feeding studies have shown that the bioavailability of folate (Fenech et al 1999(Fenech et al , 2005, and plasma levels of betaine and other methyl donors (Keaveney et al 2015) are enhanced following consumption of aleurone-enriched breads. Interestingly, a recent in vitro study has suggested that iron availability from wholewheat bread is equal to or even greater than that from fortified white bread (Nikooyeh & Neyestani 2017). To determine whether aleurone may provide a bioavailable source of iron, we compared iron availability in vitro (using ferritin formation in Caco-2 cells as a marker for iron absorption and storage within cells) from purified aleurone and wholewheat flour (provided by B€ uhler AG, Switzerland) (Latunde-Dada et al 2014).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Furthermore, human feeding studies have shown that the bioavailability of folate (Fenech et al 1999(Fenech et al , 2005, and plasma levels of betaine and other methyl donors (Keaveney et al 2015) are enhanced following consumption of aleurone-enriched breads. Interestingly, a recent in vitro study has suggested that iron availability from wholewheat bread is equal to or even greater than that from fortified white bread (Nikooyeh & Neyestani 2017). To determine whether aleurone may provide a bioavailable source of iron, we compared iron availability in vitro (using ferritin formation in Caco-2 cells as a marker for iron absorption and storage within cells) from purified aleurone and wholewheat flour (provided by B€ uhler AG, Switzerland) (Latunde-Dada et al 2014).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…There is only one possibility to reduce the impact of the antinutritional factors on the foodstuff processing -development of technologies based on traditional procedures, verified over centuries, which allows to valorize the reserves of each particular region (15,16,17). As bread represents the most essential foodstuff in the human nutrition, it is obvious that the main tendency is led towards development of such bread making procedures that would ensure a maximum biological value of the product (18,19).…”
Section: Introductionmentioning
confidence: 99%